Efektifitas Penerapan Strategi Pembelajaran Aktif Index Card Match dan Cord Sort terhadap Hasil Belajar IPS Kelas Tinggi di Sekolah Dasar - Putri, Addini Mulya; Suzanti, Lizza; Alfarisa, Fitri (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Social studies is one of the subjects taught in elementary schools and is also a problem for students to understand the material that is in the social studies itself. The main problem that was found was how to learn it. The way of learning that is carried out by this social studies teacher always focuses on himself so that the ability or potential of the students is prevented from developing. In this problem, finally, there is a solution to be able to overcome this, one way is to use the Index card match and Card Sort learning strategies. This research was carried out employing a quantitative descriptive type of literature study or literature study in which data was obtained from scientific archive records, articles, journals, books, and the like then analyzed and the conclusions were sought which could be taken as data and which were not drawn. The results also show that the learning strategy Index card match and Card Sort are effective in social studies lessons in elementary schools. The use of Index card match and Card Sort learning strategies is also good and can be applied in all subjects in elementary schools and can improve student learning outcomes